Examining funders’ roles in responsible research and innovation of medical neurotechnology - Denis Larrivee; Jennifer French; Alberto Antonietti; Zach McKinney; Noeline W. Prins; Joana Soldado-Magraner; Michael J. Young; Laura Y. Cabrera (Journal of Responsible Innovation, 2024)
Advances in medical neurotechnology (MNT) have the potential to improve the evaluation and management of conditions of the nervous system. Meanwhile, increasing concern over ethical questions and risks posed by these technologies has prompted various institutional initiatives to examine ethical aspects of their design, development, and deployment. Funding by public agencies, foundations, and private investors plays a fundamental role in driving MNT research and development (R&D). As such, the perspectives and approaches of funders can be central in instilling and shaping the values embedded in MNTs. Responsible development and oversight of MNT requires funders to proactively prioritize the integration of ethical values in MNT. We propose a multiphase design and development process involving discrete institutional norms and organizational practices and explore how this process can enhance the funder role to address ethical challenges and promote values integration in R&D.